2005
DOI: 10.1590/s0004-27492005000100012
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade das medidas de espessura central da córnea com Orbscan II e paquímetro ultra-sônico

Abstract: Both methods are similar showing good correlation. In this study, the Orbscan II showed reliability, and this tool is extremely useful to evaluate subjects regarding refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…6 Regardless of the absolute accuracy of Orbscan measures on a living human cornea, opinions have been given that 3 repeat scans should be done "to ensure repeatability and accuracy." 7 Indeed, a number of other investigators have opted to take 3 scans when using Orbscan, 8 -14 although others have reported using just 2 scans, 6,[15][16][17][18][19][20] or even taking 5 scans. 5,21,22 In all cases, repeat scans have been used to obtain an averaged value for further analyses.…”
mentioning
confidence: 99%
“…6 Regardless of the absolute accuracy of Orbscan measures on a living human cornea, opinions have been given that 3 repeat scans should be done "to ensure repeatability and accuracy." 7 Indeed, a number of other investigators have opted to take 3 scans when using Orbscan, 8 -14 although others have reported using just 2 scans, 6,[15][16][17][18][19][20] or even taking 5 scans. 5,21,22 In all cases, repeat scans have been used to obtain an averaged value for further analyses.…”
mentioning
confidence: 99%
“…In order to reduce endothelial injury, the following alternatives have been developed: viscoelastic substances (12)(13)(14)(15) ; special surgical techniques such as, for example, nuclear prefracture; and new modalities of tip vibration at ultrasonic frequency, such as the White-star ® , Neosonix ® , dynamic rising time and torsional systems (1,2,5,6,(16)(17)(18)(19)(20)(21)(22)(23) . By the year 2000, an alternative technology was proposed for cataracts surgery (5,16,17) .…”
Section: Introductionmentioning
confidence: 99%